Ministry Of Foreign Trade And Industry Decree No. 133 Of The Year 2013 On The Amendment Of Some Provisions Of The Executive Regulations Implementing The Industrial Register Law = وزارة الصناعة والتجارة الخارجية قرار رقم 133 لسنة 2013 فى شأن تعديل بعض أحكام اللائحة التنفيذية لقانون السجل الصناعى - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.